KOMPARASI MODEL PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS DEBITUR KUPEDES BRI BANGSALSARI BERDASARKAN SUKU - Tauhid, Imam (BISMA: Jurnal Bisnis dan Manajemen, 2018)
This study compares the usage models of Kupedes credit of Bank Rakyat Indonesia (BRI) Bangsalsari Jember, between the Javanese and Madurese debtors by analyzing the effect of service quality on satisfaction and loyalty of the debtors. The population is all Kupedes debtors of Javanese and Madurese in BRI Bangsalsari Jember. The sample consists of 120 Javanese debtors and 120 Madurese debtors taken by cluster sampling, purposive sampling, and quota sampling methods. The compared models were analyzed by Structural Equation Modeling (SEM) and comparative test of the two models. The results show that for the Javanese debtors, service quality has no effect on satisfaction, service quality significantly affects loyalty, and satisfaction significantly affects loyalty. For the Madurese debtors, service quality has no effect on satisfaction, service quality has no effect on loyalty, and satisfaction significantly affects loyalty. Keywords: Service Quality, Debtor Satisfaction, Debtor Loyalty